Gender Differences in the Perception of Personalized Half-Nude Female Bodies - Silveira, Sarita; Elvers, Katrin M.; Fehse, Kai; Paolini, Marco (Frontiers in Psychology, 2017)
In the current study, we investigated how the perception of half-nude female body representations is altered by framing with information about the presented person. Images from tabloid newspapers were presented to male and female observers, and rated according to their aesthetic appeal while neurofunctional correlates were assessed using functional magnetic resonance imaging. While a generally stronger appetitive response might be expected in men, our results show a significant interaction between framing condition and gender of the observer. Men rated female bodies as more pleasing when presented without personal information, whereas women expressed more aesthetic appeal when information was added. Neuroimaging data revealed gender differences in processing body representations with additional personal information. In women, there was a stronger involvement of the anterior cingulate cortex and adjacent ventromedial prefrontal cortex, and in male observers a higher engagement of the bilateral inferior parietal cortex, when compared to each other respectively. These gender differences in framing effects particularly highlight higher aesthetic appeal and reward processing in women when female bodies are personalized.